Autolysosomal activation combined with lysosomal destabilization efficiently targets myeloid leukemia cells for cell death - Shah, Harshit; Stankov, Metodi; Panayotova-Dimitrova, Diana; Yazdi, Amir; Budida, Ramachandramouli; Klusmann, Jan-Henning; Behrens, Georg M. N. (Frontiers in Oncology, 2023)
Introduction Current cancer research has led to a renewed interest in exploring lysosomal membrane permeabilization and lysosomal cell death as a targeted therapeutic approach for cancer treatment. Evidence suggests that differences in lysosomal biogenesis between cancer and normal cells might open a therapeutic window. Lysosomal membrane stability may be affected by the so-called ‘busy lysosomal behaviour’ characterized by higher lysosomal abundance and activity and more intensive fusion or interaction with other vacuole compartments. Methods We used a panel of multiple myeloid leukemia (ML) cell lines as well as leukemic patient samples and updated methodology to study auto-lysosomal compartment, lysosomal membrane permeabilization and lysosomal cell death. Results Our analyses demonstrated several-fold higher constitutive autolysosomal activity in ML cells as compared to human CD34+ hematopoietic cells. Importantly, we identified mefloquine as a selective activator of ML cells' lysosomal biogenesis, which induced a sizeable increase in ML lysosomal mass, acidity as well as cathepsin B and L activity. Concomitant mTOR inhibition synergistically increased lysosomal activity and autolysosomal fusion and simultaneously decreased the levels of key lysosomal stabilizing proteins, such as LAMP-1 and 2. Discussion In conclusion, mefloquine treatment combined with mTOR inhibition synergistically induced targeted ML cell death without additional toxicity. Taken together, these data provide a molecular mechanism and thus a rationale for a therapeutic approach for specific targeting of ML lysosomes.